Proceedings of the 25th ACM International on Conference on Information and Knowledge Management 2016
DOI: 10.1145/2983323.2983692
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Stability of Noisy Networks through Centrality Measures and Local Connections

Abstract: Networks created from real-world data contain some inaccuracies or noise, manifested as small changes in the network structure. An important question is whether these small changes can significantly affect the analysis results.In this paper, we study the effect of noise in changing ranks of the high centrality vertices. We compare, using the Jaccard Index (JI), how many of the top-k high centrality nodes from the original network are also part of the top-k ranked nodes from the noisy network. We deem a network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Most graph anonymization algorithms try to minimize the number of changes. Our studies in (Ufimtsev et al, 2016;Cheon et al, 2018) have shown that the changes to the higher cores disrupt the centrality values more than changes to the periphery.…”
Section: Applications For the Proposed Methodsmentioning
confidence: 62%
“…Most graph anonymization algorithms try to minimize the number of changes. Our studies in (Ufimtsev et al, 2016;Cheon et al, 2018) have shown that the changes to the higher cores disrupt the centrality values more than changes to the periphery.…”
Section: Applications For the Proposed Methodsmentioning
confidence: 62%
“…It underscores the importance of considering the reliability of network connections in assessing overall network stability. Ufmtsev et al [27] reveal that the impact of structural noise on centrality ranks is examined. Tis study complements our approach by highlighting how minor structural changes can signifcantly infuence the stability and centrality of nodes, thereby afecting the network's resilience to disruptions.…”
Section: Assessment Of Network Stabilitymentioning
confidence: 99%
“…Tis section evaluates four types of centrality in the directed, weighted network: degree centrality, closeness centrality, betweenness centrality, and eigenvector centrality. Tis is echoed in the work of Ufmtsev et al [27], who emphasize the impact of centrality measures on understanding the stability of networks, especially under conditions of noise and disturbance. Tis section evaluates four types of centrality in the directed, weighted network: degree centrality, closeness centrality, betweenness centrality, and eigenvector centrality.…”
Section: Centrality Measuresmentioning
confidence: 99%
“…As a first step, we note that if most of the shortest paths pass through the innermost core, then the high centrality vertices would also be part of the innermost core. Moreover, if these vertices are tightly connected to each other, they can enhance each others' centrality values [37]. Thus, a dense innermost core through which most of the shortest paths pass provides us a smaller subset in which to search for high centrality vertices.…”
Section: Our Hypothesismentioning
confidence: 99%